Pengaruh asupan serat dan lemak terhadap keberhasilan ovulasi pada policystic ovary syndrome (PCOS) yang dilakukan induksi ovulasi dengan klomifen sitrat - ABID, Husnul ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Background : The treatment of infertile women with polycystic ovary syndrome (PCOS) is surrounded by many controversies. Before any intervention is initiated, preconceptional councelling should be provided emphasing the importance of life style, especially weight reduction and exercise in overweight women. Diet was one of factorswhich has a relationship with hiperandrogenism in women with PCOS. Objectives : To analyze women with PCOS who has relation with fiber and fat consumption and successfull of ovulation in women with PCOS. Design : Analytic descriptive with cross sectional approach is used. Material and methods : The subject in this study were women with PCOS aged 15 – 45 years in dr. Sardjito Hospital Yogyakarta and selected by consecutive sampling design from August 2008 – February 2010. Rotterdam 2003 as diagnostic criteria was applied. As much as40respondents meeting the eligibility criteria were enrolled.They were interviewed fiber and fat consumption by using 24 hour food recall in two consecutive times. Serial ultrasound was applied to know the succesfull of ovulation. Results: There is no significant difference in analysis between confounding variable age and BMI (RR: 1,33; 95% CI: 0,42– 4,19; p=0,24) and (RR: 0,72; 95% CI: 0,25 – 2,06: p=0,37). In this study show age and BMI were not influencing the succesfull of ovulation (p<0,05). There is no statistical difference between fiber and fat intake to influence ovulation (RR: 1,29; 95% CI: 0,28 – 5,92: p=0,10) and (RR: 2,17; 95% CI: 0,98 – 4,81; p=3,61). After controlling age and IMT a multivariate analysis with logistic regression showed that fiber and fat have no correlation to enhance the succesfull of ovulation . Conclusions: There are not significant difference in analysis between fiber and fat intake to enhance the succesfull of ovulation.